Enhancer evolution and the origins of morphological novelty. (August 2017) - Rebeiz, Mark; Tsiantis, Miltos
Highlights: Genome-wide and single gene studies have revealed a variety of mechanisms by which new expression patterns arise. Studying newly evolved morphologies at the level of their regulatory sequences illuminates regulatory network history. Pleiotropy can arise through both wholesale network cooption and expansion of individual regulatory sequence activity. Discrete changes in regulatory sequences underlie morphological novelty in both animals and plants. Abstract : A central goal of evolutionary biology is to understand the genetic origin of morphological novelties—i.e. anatomical structures unique to a taxonomic group. Elaboration of morphology during development depends on networks of regulatory genes that activate patterned gene expression through transcriptional enhancer regions. We summarize recent case studies and genome-wide investigations that have uncovered diverse mechanisms though which new enhancers arise. We also discuss how these enhancer-originating mechanisms have clarified the history of genetic networks underlying diversification of genital structures in flies, limbs and neural crest in chordates, and plant leaves. These studies have identified enhancers that were pivotal for morphological divergence and highlighted how novel genetic networks shaping form emerged from pre-existing ones.